STRATEGI PENINGKATAN SKALA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DI KOTA PADANG - Ika Yuanita; Nurhayati Nurhayati; Eva Yoyet (Politeknik Negeri Padang, 2018)
The objectives of the research are to identify the potencies and characteristics of cracker SMEs and to analyze internal and external factors of upgrading enterprises scale strategies in Padang Munipacility. Data were analyzed by strengths, weaknesses, opportunities, and threats (SWOT) and quantitative strategic planning matrix (QSPM) methods. Cracker SMEs have the similar characteristics in production, marketing, human resources, finance, legal, and supports from relevant institutions. Also, the production uses semi-manual process, SMEs sell their products through direct selling, store offline and online with a limited market share with employees are 2-15 people. Capital is relatively low and a few unit of cracker SMEs have legalityand certification. Local government plays an important role in developing cracker SMEs upgrading enterprise scale. The main strength is local taste products, and the main weakness is a limited area of marketing. The major opportunity as culinary tourism, but they also face tight competition as the main threat. The development strategy of food SMEs competitiveness includes increasing cooperation to maintain continuity of raw materials between regions, developing centers of SME products, and increasing role of local governments, private companies or stateowned enterprises, and universities.